Pengaruh Senam Pendidikan Kesehatan Tentang Morbili Terhadap Pengetahuan Ibu Yang Mempunyai Balita Di RW 10 Dan 11 Desa Babakan Wilayah Kerja Puskesmas Pakutandang - Asep Solihat; Ida Widyanti (Jurnal Rumpun Ilmu Kesehatan, 2021)
Morbili becomes one of the leading causes of death of children under five years. One of the efforts reductions the mortality rate is health promoting through provision of health education on immunization. Mother as a target in this effort is very effective because it has an important role in making health care decisions on children and families. The aim of research was determine the effect of health education on the knowledge morbili’s mothers with children. This type of research has a quasi-experimental research design with pre and post test without control design. Population of this study was 63 mothers with children in RW 10 and 11 Babakan Village of Pakutandang PHC. The sample was 13 participants, while the technique of sampling was using a purposive sampling. Test the validity of the questionnaire ranged from .646-.905 with a .896 reliability. Data collection tool is questionnaire knowledge about morbili. The results of the study, analyzed by t-test showed that before being given health education almost half of participants (46.1%) had knowledge level is less than the average is 8.3, whereas after being given health education almost all knowledge of the participants (76.9%) experienced an increase in average 15.7. So statistically revealed significant difference between the knowledge before and after about morbili in mothers, with ≤ ρ = .000  = .005. Suggestion. Public health centre shoud be increasing the dissemination and promotion of health to mothers who have children on the importance of disease prevention through immunization periodically.